Social Impact Development Company Trends: from CSR to ESG - Martin, Zsarnoczky; Szergej, Vinogradov (Magyar Gerontológia, 2023)
The latest social processes impacting companies' cultural behaviour have been studied in order to help us clarify and value the social ecosystem that benefits people. Studies have analyzed the full suite of Corporate Social Responsibility, Sustainability, and Environment, Social, and Governance processes provided by the best companies' practices available. Corporate Social Responsibility is a common strategy of management where companies voluntarily take into consideration the environmental and social aspects as consequences of their activity. The idea of Corporate Social Responsibility started among big and international firms at the beginning and became a very popular management theory. Nowadays, small and medium-sized companies are in favour of using it as their daily routine. The management strategies, e.g. CSR, sustainability, ESG enables the companies to work more efficiently and stable.